1970
DOI: 10.2307/1935391
|View full text |Cite
|
Sign up to set email alerts
|

Genetic vs. Environmentally Induced Variation in Medusahead (Taeniatherum Asperum [Simokai] Nevski)

Abstract: The influences of seed—nursery environment upon genecological characteristics of 20 medusahead strains was studied. Environmentally induced variation was observed in germination, early height development, and winter survival. Small, but significant, variation in dates of spike emergence and anthesis, caused by differences in seed—nursery environment, were observed. Results suggest that the common practice of attaching genecological significance to wild—grown seed may be subject to error, especially in germinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1

Year Published

1972
1972
1992
1992

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 11 publications
0
18
1
Order By: Relevance
“…Attaching genecological significance to the performance of seed taken from natural populations has been criticized by Nelson, Harris, and Goebel (1970). They have indicated that seed must be grown in uniform gardens before genecological comparisons can be made.…”
mentioning
confidence: 99%
“…Attaching genecological significance to the performance of seed taken from natural populations has been criticized by Nelson, Harris, and Goebel (1970). They have indicated that seed must be grown in uniform gardens before genecological comparisons can be made.…”
mentioning
confidence: 99%
“…In a number of plant species with extensive distributions, individuals of each local population are found to be adapted through natural selection to the environment in the local habitat (Turesson 1922;Clausen et al 1940aClausen et al , 1940bMcMillan 1959;Mooney and Billings 1961 ;McNaughton 1966). However, numerous studies of the population biology of weedy species reveal that a variety of adaptive strategies are used by different species in successfully colonizing and persisting in different habitats (Hulbert 1955;McKell et al 1962;Imam and Allard 1965;Ramakrishnan 1968 ;Jain 1969;Jain et al 1970;Nelson et al 1970). For example, within the genus Auena in central California, populations of A. fatua show habitat-correlated genetic variation, while A. barbata populations show much less genetic variation and greater phenotypic plasticity (Jain 1969).…”
Section: Introductionmentioning
confidence: 99%
“…Increased soil moisture increased the seed weight of alfalfa (lysdal, 1946; Abu-Shakra et al , I969), barley (Wells and Dubetz.,I966), flax (Dillman, 1943), medusahead (Nelson et al , 1970), and late varieties of wheat (Chinoy,I962). Seed weight in early varieties of wheat was not influenced by moisture (Bingham,196?1 Chinoy,I962), Seed weight of most grain crops (Ryle, 1966), rice (Murata,I966), com (Davide, I96I), and side-oats grama (1966) reported an increase in seed weight of rice with nitrogen applica tions if the plant density was low, Bingham (196?…”
Section: Environmental Influences On Seed Sizementioning
confidence: 99%
“…In spaced plantings, red clover yields were proportional to the initial seed weight (Black, 1959)» Initial seed weight accounted for 2,5-4.5^ of the observed variation in the seed production of mature plants of spring wheat (Austenson and Walton, 1970). Larger and heavier seed of sunflower produced stronger plants with greater yield (Govedarov, 1971), while initial seed size had no effect on the yield of medusahead (Nelson et al , 1970).…”
Section: Environmental Influences On Seed Yieldmentioning
confidence: 99%
See 1 more Smart Citation